Effective and Efficient Stand Magnifier Use in Visually Impaired Children - Liebrand-Schurink, Joyce; Cox, Ralf F. A.; van Rens, Ger H. M. B.; Cillessen, Antonius H. N.; Meulenbroek, Ruud G. J.; Boonstra, Frouke N. (Frontiers in Psychology, 2016)
Purpose. The main objective of this study was to analyze the effectiveness and efficiency of magnifier use in children with visual impairment who did not use a low vision aid (LVA) earlier, in an ecologically valid goal-directed perceptuomotor task. Methods. Participants were 29 4-to-8 year old children with visual impairment and 47 age-matched children with normal vision. After seeing a first symbol (an LH symbol), children were instructed to (1) move the stand magnifier as quickly as possible towards a small target symbol (another LH symbol that could only be seen by using the magnifier), (2) compare the two symbols, and (3) move the magnifier to one of two response areas to indicate whether the two symbols were identical. Performance was measured in terms of accuracy, response time, identification time, and movement time. Viewing distance, as well as hand and eye dominance while using the magnifier was assessed. Results. There were no significant differences between the two groups in accuracy, reaction time, and movement time. Contrary to the prediction, children with visual impairment required less time to identify small symbols than children with normal vision. Both within-subject and between-subject variability in viewing distance were smaller in the visually impaired group than in the normally sighted group. In the visually impaired group, a larger viewing distance was associated with shorter identification time, which in turn was associated with higher accuracy. In the normally sighted group, a faster movement with the magnifier and a faster identification were associated with increasing age. Conclusions. The findings indicate that children with visual impairment can use the stand magnifier adequately and efficiently. The normally sighted children show an age related development in movement time and identification time and show more variability in viewing distance, which is not found in visually impaired children. Visually impaired children seem to choose a standard but less adaptive strategy in which they primarily used their preferred hand to manipulate the magnifier and their preferred eye to identify the symbol.